Lithospheric reworking and thinning by cyclical continental extension: a synthesis of Cretaceous extensional domes in the South China Block - Chu, Yang; Liu, Tanjie; Lin, Wei; Meng, Lingtong; Feng, Zhentian; Wei, Wei; Ji, Wenbin; Xue, Zhenhua (Comptes Rendus. Géoscience)
Continents with cratonic cores can resist deformation, and thus survive billions of years in the geological record. Tectonic reworking is a significant process that weakens and destructs cratons, but our understanding of the process remains incomplete. In the South China Block, Mesozoic cyclical tectonics destructed a large portion of its cratonic lithosphere. Here, we synthesized the structural evolution of extensional domes and illustrated the process of lithospheric thinning. Unlike the previous rapid, one-cycle delamination model, we propose a new model that multicycle compression and extension progressively destructed the lithosphere, which reconciles both surface geology and deep process.